Cranioplasty infection in porous hydroxyapatite: Potential antibacterial properties - Ismail Zaed; Corrado Iaccarino; Francesca Faedo; Laura Grillini; Elisabetta Galassi; Alessandro Dotti; Angelo Nataloni; Francesca Carolina Mannella; Andrea Cardia (Journal of Applied Biomaterials & Functional Materials)
Introduction: Intensive research is dedicated to the development of novel biomaterials and medical devices to be used as grafts in reconstructive surgery, with the purpose of enhancing their therapeutic effectiveness, safety, and durability. A variety of biomaterials, from autologous bone to polymethylmetacrylate, polyether ether ketone, titanium, and calcium-based ceramics are used in cranioplasty. Porous hydroxyapatite (PHA) is reported as a possible material for bone reconstruction, with good signs of biocompatibility, osteoconductive and osteointegrative properties. In the present paper we studied the possible antibacterial properties of PHA in a laboratory test in order to provide a possible overview of the occurrence of post-operative infections in PHA cranioplasty. Method: The test method has been designed to evaluate the potential antimicrobial activity of specimens under dynamic contact conditions to overcome difficulties in ensuring contact of inoculum to the specimen surface. The test was conducted using Staphylococcus aureus ATCC6538 as a bacterial strain. Results: Two experimental sets were performed to evaluate the antimicrobial properties of the specimens against two different Staphylococcus aureus concentrations. The first preliminary test (a) verified the antibacterial property at 0, 1, 2, and 4 h of contact time; the second confirmatory test (b) was repeated to verify the antibacterial property at 0, 4, 8 h. In the first experiment, after the first hour of contact, the bacterial inoculum was reduced by 7.96% compared to “inoculum only,” which increased to 26.11% at the second hour, and up to 52.33% after 4 h. In the second experiment, the confirmation test showed that bacterial growth reaches maximum inhibition after 4 h of contact. At 4 h, there was a higher bacterial reduction of 72.93%, which decreased at 8 h (36.45%). Conclusion: Analyzing the growth trend of viable microorganisms under Dynamic Contact Conditions it can be seen that PHA cranioplasty appears to inhibit exponential growth by inducing bacterial stasis in the early hours of contact, reaching a maximum reduction within 4 h, in this adopted experimental condition.